The stable carbon isotope signature of methane produced by saprotrophic fungi - Schroll, Moritz; Keppler, Frank; Greule, Markus; Eckhardt, Christian; Zorn, Holger; Lenhart, Katharina (Biogeosciences, 2020)
Abstract. Methane (CH4) is the most abundant organic compound in the atmosphere and is emitted from many biotic and abiotic sources. Recent studies have shown that (CH4) production occurs under aerobic conditions in eukaryotes, such as plants, animals, algae, and saprotrophic fungi. Saprotrophic fungi play an important role in nutrient recycling in terrestrial ecosystems via the decomposition of plant litter. Although CH4 production by saprotrophic fungi has been reported, no data on the stable carbon isotope values of the emitted CH4 (δ13C-CH4 values) are currently available. In this study, we measured the δ13C values of CH4 and carbon dioxide (δ13C-CO2 values) emitted by two saprotrophic fungi, Pleurotus sapidus (oyster mushroom) and Laetiporus sulphureus (sulphur shelf), cultivated on three different substrates, pine wood (Pinus sylvestris), grass (mixture of Lolium perenne, Poa pratensis, and Festuca rubra), and corn (Zea mays), which reflect both C3 and C4 plants with distinguished bulk δ13C values. Applying Keeling plots, we found that the δ13C source values of CH4 emitted from fungi cover a wide range from −40 to −69 mUr depending on the growth substrate and fungal species. Whilst little apparent carbon isotopic fractionation (in the range from−0.3 to 4.6 mUr) was calculated for the δ13C values of CO2 released from P. sapidus and L. sulphureus relative to the bulk δ13C values of the growth substrates, much larger carbon isotopic fractionations (ranging from −22 to −42 mUr) were observed for the formation of CH4. Although the two fungal species showed similar δ13CH4 source values when grown on pine wood, δ13CH4 source values differed substantially between the two fungal species when they were grown on grass or corn. We found that the source values of δ13CH4 emitted by saprotrophic fungi are highly dependent on the fungal species and the metabolized substrate. The source values of δ13CH4 cover a broad range and overlap with values reported for methanogenic archaea, the thermogenic degradation of organic matter, and other eukaryotes.
Gesehen am 23.09.2020